The type 1 diabetes susceptibility locus Idd5 favours robust neonatal development of highly autoreactive regulatory T cells in the NOD mouse - Santamaria, Jérémy C.; Vuillier, Sylvia; Galindo-Albarrán, Ariel O.; Castan, Sarah; Detraves, Claire; Joffre, Olivier P.; Romagnoli, Paola; van Meerwijk, Joost P. M. (Frontiers in Immunology, 2024)
Regulatory T lymphocytes expressing the transcription factor Foxp3 (Treg) play an important role in the prevention of autoimmune diseases and other immunopathologies. Aberrations in Treg-mediated immunosuppression are therefore thought to be involved in the development of autoimmune pathologies but few have been documented. Recent reports indicated a central role for Treg developing during the neonatal period in the prevention of autoimmune pathology. We therefore investigated the development of Treg in neonatal NOD mice, an important animal model for autoimmune type 1 diabetes. Surprisingly, we found that, as compared to seven other commonly studied inbred mouse-strains, in neonatal NOD mice exceptionally large proportions of developing Treg express high levels of GITR and PD-1. The latter phenotype was previously associated with high Treg-autoreactivity in C57BL/6 mice, which we here confirm for NOD animals. Proportions of newly developing GITRhighPD-1+ Treg rapidly drop during the first week of age. A genome-wide genetic screen indicated involvement of several diabetes susceptibility loci in this trait. Analysis of a congenic mouse-strain confirmed that Idd5 contributes to the genetic control of GITRhighPD-1+ Treg-development in neonates. Our data thus demonstrate an intriguing and paradoxical correlation between an idiosyncrasy in Treg development in NOD mice and their susceptibility to type 1 diabetes.